Congenital heart disease screening program in elementary schools: a research-based policy - Dinarti, Lucia Kris; Hartopo, Anggoro Budi; Hadwiono, Muhammad Reyhan; Wiradhika, Abdul Majid Halim; Meliala, Andreasta; Putri, Likke Prawidya; Fajarwati, Prahesti; Anggrahini, Dyah Wulan (Universitas Gadjah Mada, 2023)
Purpose: CHD is a condition where heart abnormalities develop before birth and can lead to severe complications such as heart failure and premature death, especially among younger adults. Delayed diagnosis and treatment worsen the situation for CHD patients. Early screening can prevent CHD and ensure timely interventions. This study discusses the latest advancements in CHD screening for primary school children and the valuable insights gained from the program. Method: The CHD screening program in Yogyakarta province involved three stages: consolidation, implementation, and incorporation. During the consolidation stage, key decision-makers in the province and local health offices were involved. Primary healthcare workers and primary school teachers were trained to deliver the screening during the implementation stage. Stakeholders, health workers, and teachers were invited to discuss the results, and the Provincial Governor's office was engaged during the incorporation stage. Results: In 2018–2019, 18 CHDs were identified from 6,116 school-age children in 4 districts in Indonesia. The screening program was led by academics in the Universitas Gadjah Mada through 3 stages: consolidation, implementation, and incorporation. Strong collaboration with local stakeholders has contributed to the program's success in engaging 130 schools, 60 community health centers, and 190 health workers. Several opportunities for improvement are: strengthening the capacity and number of health providers at health centers to screen CHDs using 12-lead electrocardiography, addressing patients' reluctance to visit the health facility due to the COVID-19 pandemic, and motivating parents to have their children checked. Conclusion: CHD screening using 12-lead electrocardiography and auscultation should be part of primary school health screenings. Academics can train health workers, and local governments can provide funding and prepare health facilities for follow-up treatment.